N.Ya. Danilevsky and M.E. Saltykov-Shchedrin about Russia and Europe - Yu.A. Martynova; D.E. Martynov (Ученые записки Казанского университета: Серия Гуманитарные науки)
This article discusses the essays by M.E. Saltykov-Shchedrin from his novels “The Golovlevs” and “Abroad” in the context of N.Ya. Danilevsky’s theory of cultural-historical types. Both of these writers can be defined as religious, though N.Ya. Danilevsky considered the possibility of proving the divine principle in nature using scientific methods. He identified specific cultural-historical types in world history as a manifestation of divine harmony, to which all world structures are subject. Definite political conclusions were drawn from this general construct: cultural-historical types of different genesis cannot interact or successfully transfer a system of values to each other. Russia’s attempt to join Europe , as viewed by N.Ya. Danilevsky, may only deprive it of political independence, “strength, integrity, and unity of the state organism.” M.E. Saltykov-Shchedrin, who had good knowledge of modern Germany and France “from the inside”, also developed a typology of the way of life and culture of Europe and Russia, but comprehended them satirically in the form of “philosophical buffoonery”. His reasoning about the absence of any native system for educating new generations in Russia and the negativism of “Europeanism” represents the viewpoint of writers of his time and subsequent eras, such as I.A. Goncharov, V.V. Rozanov, and V.G. Yanchevetsky holding a relatively marginal position. Similarly to N.Ya. Danilevsky, M.E. Saltykov-Shchedrin denied the so-called universal values by assuming that the lifestyle and political system are largely shaped by cultural particularities.